Predictive value of Caprini risk assessment model, D-dimer, and fibrinogen levels on lower extremity deep vein thrombosis in patients with spontaneous intracerebral hemorrhage - Fang, Xia; Shen, Yi; Wang, Mei; Dai, Lihong; Shi, Linlin; Zhang, Feng; Chen, Congcong; Yuan, Yuan (Frontiers in Neurology, 2024)
Research indicates that individuals experiencing hemorrhagic stroke face a greater likelihood of developing lower extremity deep vein thrombosis (DVT) compared to those with ischemic stroke. This study aimed to assess the predictive capacity of the Caprini risk assessment model (RAM), Ddimer (D-D) levels, and fibrinogen (FIB) levels for lower extremity DVT in cases of spontaneous cerebral hemorrhage (sICH). Methodology involved a retrospective analysis of medical records from all sICH patients admitted to Shanghai General Hospital between June 2020 and June 2023. Within 48 hours of admission, patients underwent routine screening via color Doppler ultrasonography (CDUS). Patients were categorized into DVT and control groups based on the occurrence of lower extremity DVT during hospitalization. Differences in Caprini RAM, D-dimer, and FIB levels between the two groups were compared. The sensitivity and specificity of combined Caprini RAM, peripheral blood D-dimer, and FIB in predicting lower extremity DVT in sICH patients were analyzed. Receiver operating characteristic (ROC) curves assessed the overall predictive accuracy of Caprini RAM, D-D, and FIB levels.Results from the study involving 842 sICH patients revealed 225 cases with DVT and 617 without DVT. Caprini RAM, D-D, and FIB levels were significantly higher in the DVT group compared to the control group (P<0.05). Sensitivity values for Caprini RAM, D-D, and FIB levels in predicting lower extremity DVT in sICH patients were 0.920, 0.893, and 0.680, respectively, while specificities were 0.840, 0.680, and 0.747. The ROC curve analysis demonstrated an area under the curve (AUC) of 0.947 for combined DVT prediction, with 97.33% sensitivity and 92.00% specificity, indicating superior predictive value compared to individual applications of Caprini RAM, D-D, and FIB.In conclusion, the combined utilization of Caprini RAM, D-D, and FIB levels holds significant clinical relevance in predicting lower extremity DVT in sICH patients.